Improving Freight Transit and Logistics Performance of the Trans-Caucasus Transit Corridor : Strategy and Action Plan - World Bank (World Bank, Washington, DC, 2020)
This strategy and action plan put forward a guiding vision for the trans-Caucasus transit corridor (CTC), with a focus on the part to be played by Georgia and Azerbaijan to develop the CTC into a competitive alternative to other regional routes for the transport of goods, especially for containerized goods between China and Europe, and to promote a solid and professional transport system in the two countries, in association with neighboring economies (Kazakhstan, Turkey, and others). The implementation of this strategy and action plan will ensure that the corridor is operated in an efficient way that augments the economic benefits of the infrastructure works, attracting traffic, and reducing operating costs. The strategy outlines five strategic targets that define a path to successfully navigate the institutional and functional changes presented by the action plan: (i) reduce major nonphysical barriers to the efficiency of the CTC; (ii) remove physical barriers, by, for example, interconnecting infrastructure more efficiently, and installing intermodal facilities; (iii) improve institutional frameworks, including the establishment of a coordinating body to streamline and strengthen governance transport along the CTC and promote and support its development; (iv) develop a transnational regulatory framework; and (v) build capacity in the logistics sector.